FINANCIAL REPORT SEBAGAI ALAT UKUR DAN CONTROL PERFRMANCE PERUSAHAAN - Lubis, Hilman (EDUTECH CONSULTANT, 2018)
Accounting is the process of identifying, measuring, summarizing and classifying economic events or transactions to produce financial information / quantitative financial statements that are used by the user in decision making. Financial Report is the final result of the accounting process needed by the company as a communication tool that is expected to be able to provide information on the company's financial condition that will be used by internal parties and extern companies in decision making.